Global human rights and contextualised civic learning: a case study of human rights education in Japan - Meyer, TG (2017)
While global human rights knowledge has become a central facet of curricula used to shape multicultural societies and develop cosmopolitan citizenry, such knowledge is shaped by sociopolitical context. Japan has a long history of incorporating human rights concepts into its citizenship curriculum; however, this curriculum is produced in a political context where there is resistance to extending rights to minorities and the disadvantaged, and where there are renewed attempts to emphasise traditional Japanese cultural values through education. Potential tensions have been recognised, yet little has been written about educational knowledge as end product, or its role in informing learner and teacher understanding of human rights. Intentions to promote inclusivity and new communal identities notwithstanding, this work establishes that the recontextualising discourse of human rights within Japan’s school curriculum, as a discourse that regulates identity and citizenship, portrays the rights of marginalised and non-Japanese identities as privileges extending beyond the norm of society, while at the same time implicitly denying ethnic Japanese individuals full access to rights language. Thus, while learners regard human rights of value, many are less receptive and empathetic to rights claims made by non-like others, and are likely to consider society as incapable of embracing diversity. Human rights concepts possess symbolic value and weight; however, their symbolic importance can be easily embedded within particularistic notions of identity and nationality to ends contrary to multiculturalism and cosmopolitanism, which for this research was witnessed in their transformation into tools for cultural and political legitimacy by the Japanese State. This research arrives at these conclusions through a systemic, holistic analysis of human rights learning in Japan that ties official knowledge to instructional and learning outcomes. This research is first a mixed-method policy sociology utilising computer-based analytical techniques to examine the structure and content of human rights knowledge within upper-secondary social studies textbooks representing Japan’s official curriculum. This is followed by a comparative case study of two upper-secondary institutional sites of human rights learning, an academic, public coeducational western Japan senior high school, and a private Tokyo girls’ senior high school, the primary differentiation being that the western Japan school is an explicit site of human rights learning, applying its own content and pedagogic practice as part of a specialised human rights curriculum designed to supplement the official curriculum. This research not only has implications for Japan in yielding a greater understanding of how the curriculum engages and reproduces identities and to what end, but also potentially to understand how similar tensions and contradictions between universal and particular play out in other national, State-sponsored education contexts.